Penerapan Modul Ajar dalam Model Pembelajaran Flipped Classroom untuk meningkatkan Literasi Digital Siswa Sekolah Menengah Kejuruan - Lestari, Ika Rokhasari; Anifah, Lilik; Buditjahjanto, I Gusti Putu Asto (Jurnal Studi Guru dan Pembelajaran, 2024)
Challenges encountered during the Industrial Era 4.0 include information technology security, the reliability and stability of production machinery, insufficient skills, resistance to change among stakeholders, and significant job displacement due to automation. This study aimed to investigate variations in digital literacy skills between students using modules and those not using modules in a flipped classroom setting at SMKN 4 Bojonegoro. The research employed experimental quantitative methods, utilizing observation and student test results for data collection. Data analysis involved the use of an independent sample T-TEST. The results of the T-TEST indicated that the average score for the module group was 78.53 with 30 participants, while the non-module group averaged 73.3 with 30 participants, resulting in a difference (diff) of 5.2. The statistical significance (p-value) in the Pr(T>t) row (under Ha: diff > 0) was found to be less than 0.05, confirming a statistically significant difference between the two groups. This study concludes that students' digital literacy skills in the software engineering program at SMKN 4 Bojonegoro are higher when using teaching modules in flipped classroom learning compared to those who do not use modules. This research contributes to the educational database at SMKN 4 Bojonegoro, particularly for class XI students in the software engineering expertise program.